Estimated thresholds (est dBHL) for auditory evoked potentials with narrowband CE-Chirp® stimuli - Fuentes, Miguel; Barrientos, Robinson; Bravo, Sofía (My University, 2024)
ABSTRACT Purpose: to correlate pure-tone audiometry thresholds with electrophysiological thresholds, using NB CE-Chirp® stimuli in listeners aged 18 to 30 years from Santiago, Chile, and determine the estimated threshold at 500, 1000, 2000, and 4000 Hz. This can contribute to the battery of objective and subjective tests applicable to children, aiding the timely detection and implementation before 3 months old, as recommended by the Joint Committee on Infant Hearing. Methods: a quantitative, nonexperimental study with a sample of 30 hearing subjects, aged 18 to 30 years. The Pearson´s correlation test was applied, with a significance p-value of 0.01. Results: higher frequencies (2000 and 4000 Hz) have lower correction factors than medium and lower frequencies (1000 and 500 Hz), which tend to be higher as the frequency is lower. Conclusions: the study obtained the following estimated thresholds: 15 dB at 500 Hz, 10 dB at 1000 and 2000 Hz, and 5 dB at 4000 Hz.
Keywords: auditory threshold; evoked potentials, auditory, brain stem; electrophysiology